Spark of opal - Clark, Mavis Thorpe (New York : The Macmillan Company, 1973)
Discouraged that their family has not made its fortune in the Australian opal fields, a teen-age brother and sister make a dangerous final attempt to change the family's luck.
Opal town -- After eight years -- Water-hole creek -- The stolen compressor -- Spider-holes of men -- The opal cutter -- Too late! -- Kathy's news -- Judo and karate -- Dangerous ideas -- Ruthe -- "Liz shouldn't have come!" -- A plan at last! -- An old windlass -- Seventy feet down -- Mike confronts melikos -- Nikos brings some news -- Off again-on again -- Carl and the future -- The end of the year.
Keywords: AUSTRALIAN FICTION -- OPALS